Exploring Online Learning Tools Used by EFL Teachers during the COVID-19 Pandemic - Mariska Intan Sari; Aura Amalia Putri (Universitas Muhammadiyah Yogyakarta, 2022)
COVID-19 pandemic has affected many sectors of human life, including the educational sector. This situation has forced the government to impose the School-from-Home policy for all levels of education in Indonesia since March 2020. In this situation, teachers need to be aware of this change and adapt to the situation. The use of media in learning matters since the learning process is switched to online learning. Thus, this paper aims to explore the online learning tools utilized by EFL teachers and EFL teachers’ consideration in choosing online learning tools during the COVID-19 pandemic. This research employed a qualitative approach by conducting in-depth interviews with five EFL teachers from five different state senior high schools in Yogyakarta Special Region, who have taught English for at least two years and have used online learning tools during the COVID- 19 pandemic. This research found six types of online learning tools used by the EFL teachers: learning management systems, assessment tools, chat and messages, video learning and sharing platform, content maker, and video conferencing tools. Moreover, concerning the teachers’ considerations in utilizing these online learning tools, they explained that they should be easy to use, accessible, cost-effective, interesting, and lightweight. Other teachers could also use these considerations to choose the online learning tools utilized in their teaching and learning processes.